Glycopeptide Resistance in Gram-Positive Cocci: A Review - S. Sujatha; Ira Praharaj (Interdisciplinary Perspectives on Infectious Diseases)
Vancomycin-resistant enterococci (VRE) have emerged as important nosocomial pathogens in the past two decades all over the world and have seriously limited the choices available to clinicians for treating infections caused by these agents. Methicillin-resistant Staphylococcus aureus, perhaps the most notorious among the nosocomial pathogens, was till recently susceptible to vancomycin and the other glycopeptides. Emergence of vancomycin nonsusceptible strains of S. aureus has led to a worrisome scenario where the options available for treating serious infections due to these organisms are very limited and not well evaluated. Vancomycin resistance in clinically significant isolates of coagulase-negative staphylococci is also on the rise in many setups. This paper aims to highlight the genetic basis of vancomycin resistance in Enterococcus species and S. aureus. It also focuses on important considerations in detection of vancomycin resistance in these gram-positive bacteria. The problem of glycopeptide resistance in clinical isolates of coagulase-negative staphylococci and the phenomenon of vancomycin tolerance seen in some strains of Streptococcus pneumoniae has also been discussed. Finally, therapeutic options available and being developed against these pathogens have also found a mention.